Organic matter enrichment of the Chang 7 member in the Ordos Basin: Insights from chemometrics and element geochemistry. (January 2022) - Shi, Jun; Zou, Yan-Rong; Cai, Yu-Lan; Zhan, Zhao-Wen; Sun, Jia-Nan; Liang, Tian; Peng, Ping'an
Abstract: The lacustrine black shales of the Chang 7 member are the main source rocks and the most important unconventional (shale oil) petroleum resources in the Ordos Basin, North China. A series of continuous core samples was analysed for main, trace, and rare earth elements. The development of thin or laminar tuffs and tuffaceous mudstones and the enrichment of Fe, Mn, and other elements demonstrate that the Chang 7 member was influenced by event deposition, such as volcanic and hydrothermal activity. The ancient lake had brackish water and a relatively high sedimentation rate during the deposition of the Chang 7 member. The palaeoclimate in the early stage was warmer and wetter than that in the middle-late stage of the Chang 7 period. The geochemical proxies for palaeoproductivity and palaeoredox indicate that the ancient lake had a relatively high primary productivity with an anoxic to euxinic sulphide bottom water in the Chang 7 3 stage, which decreased to dyoxic-oxic water during the Chang 7 1+2 periods. A parameter dataset comprising 11 elemental proxies related to the reconstruction or evaluation of the depositional environment and palaeoproductivity was analysed using principal component analysis (PCA). The first principal component (PC1) accounted for 59.88% of the total variance in the original dataset and mainly represented the characteristics of palaeoproductivity and redox conditions; thus, it can be interpreted as an indicator of these factors. Based on the excellent positive linear correlation between the total organic matter content of the Chang 7 samples and the PC1 scores, the enrichment of organic matter in the Chang 7 member was mainly controlled by palaeoproductivity and the preservation environment. PCA is an effective method for dimensionality reduction and visualisation of multi-element geochemical data, which allows for a more comprehensive and in-depth understanding of geological samples. This work provides a practical application of chemometrics in elemental geochemistry. This can serve as a model for other studies. Highlights: Insight into organic matter enrichment by combining PCA with element geochemistry. The primary paleoproductivity of the Chang 7 member in the Ordos Basin was evaluated. The paleosedimentary environment of the Chang 7 member was reconstructed. The organic matter enrichment of Chang 7 member was controlled by paleoproductivity and preservation.